Data Analytics for Employees Dashboard to Improve Efficiency and Performance of Employees - Kaur, Rishamdeep (My University, 2018)
It is a Test Platform Usage Dashboard, as it is a Test Platform, the Higher Management should be enabled to view how effectively being utilized, relocate the underutilized platforms to areas in need. Increasing the resource utilization and effectiveness, thus reducing the cycle time and saving costs. However, the Management did not have access to view, utilize and relocate the underutilized platforms to areas in need. CNE is internally developed Test Platform. Test Platform is costly and scare resource. With this dashboard we are enabling the higher Management to view how effectively being utilized, relocate the underutilized platforms to areas in need. Increasing the resource utilization and effectiveness, thus reducing the cycle time and saving costs.
Master of Engineering- CSE
Keywords: Dashboard; GUI